Civilization of marital violence in the New Granada within the framework of social mobility strategies at the end of the Viceregal period - López Jerez, Mabel Paola (Cuadernos de Historia, 2021)
In New Granada, despite the lack of love or repression, the family environment was structurally crossed by interpersonal aggression, in the late eighteenth and early nineteenth centuries, within the framework of social mobility strategies of the time. A civilizing process of conjugal violence operated that produced a decrease in cases among the white peninsular and the creoles, while the events were concentrated among the poor mestizos, the indigenous people, and the free blacks. The wealthy mestizos, meanwhile, were the hinge between the upper and lower classes. The backdrop for this social phenomenon would be the enlightened ideas, which, brought from Europe and appropriated by the Royal Court and by New Granada lawyers, distorted the violence against women, condemned it and called for a more equal relationship between the spouses.